Loud noise-exposure changes the firing frequency of subtypes of layer 5 pyramidal neurons and Martinotti cells in the mouse auditory cortex - Nogueira, Ingrid; Lima, Thiago Z.; Malfatti, Thawann; Leao, Katarina E. (Frontiers in Aging Neuroscience, 2023)
Loud noise-exposure can generate noise-induced tinnitus in both humans and animals. Imaging and in vivo studies show that noise exposure affects the auditory cortex; however, cellular mechanisms of tinnitus generation are unclear. Here we compare membrane properties of layer 5 (L5) pyramidal cells (PCs) and Martinotti cells expressing the cholinergic receptor nicotinic alpha 2 subunit gene (Chrna2) of the primary auditory cortex (A1) from control and noise-exposed (4-18 kHz, 90 dB, 1.5 hr, followed by 1.5 hr silence) 5-8 week old mice. PCs were furthermore classified in type A or type B based on electrophysiological membrane properties, and a logistic regression model predicting that afterhyperpolatization (AHP) and afterdepolarization (ADP) are sufficient to predict cell type, and these features are preserved after noise trauma. One week after a loud noise-exposure no passive membrane properties of type A or B PCs were altered but principal component analysis showed greater separation between type A PCs from control and noise-exposed mice. When comparing individual firing properties, noise exposure differentially affected type A and B PC firing frequency in response to depolarizing current steps. Specifically, type A PCs decreased initial firing frequency in response to +200 pA steps (p = 0.020) as well as decreased steady state firing frequency (p = 0.050) while type B PCs, on the contrary, significantly increased steady state firing frequency (p = 0.048) in response to a +150 pA step one week after noise exposure. In addition, L5 Martinotti cells showed a more hyperpolarized resting membrane potential (p = 0.04), higher rheobase (p = 0.008) and an increased initial (p = 8.5 x 10-5) and steady state firing frequency (p = 6.3 x 10-5) in slices from noise-exposed mice compared to control. These results show that loud noise can cause distinct effects on type A and B L5 PCs and inhibitory Martinotti cells of the primary auditory cortex one week following noise exposure. As the L5 comprises PCs that send feedback to other areas, loud noise exposure appears to alter levels of activity of the descending auditory system.